Evaluation of cytotoxic, antimicrobial, and antioxidant activi-ties of Echium italicum L. in MCF-7 and HepG2 cell lines - Dilek Arslan Atessahin; Semih Dalkilic; Lütfiye Kadioglu Dalkilic; Dudu Bayindir; Elif Cetinkaya (International Journal of Plant Based Pharmaceuticals)
The use of plants for medicinal purposes from past to present continues as traditional treatments. One of these plants, Echium species, is known for its high phytochemical content and its use as a sedative or in colds. In this study, the antibacterial, antioxidant and anticancer properties of Echium italicum L. were investigated. Its anticancer effect was tested in HepG2 (liver cancer) and MCF-7 (breast cancer) cell lines. Its antimicrobial effect was also investigated in Candida albicans, Klebsiella pneumoniae, Escherichia coli, Bacillus megaterium and Staphylococcus aureus. The results showed that the highest cytotoxic effect was observed in the HepG2 cell line with 23% dead cell count. This suggests that the plant is especially effective in liver cancer cell lines. It was found that the extract prepared in hexane had the largest inhibition zone diameter (15 mm) against C. albicans in terms of antibacterial activity. The highest DPPH radical scavenging activity was observed in methanol extract with 37.6%. Considering the IC50 value in DPPH, hexane extract exhibited better activity than methanol extract (IC50 = 20.7 µg/ml). The data obtained from the study indicate that E. italicum has cytotoxic, antimicrobial and antioxidant effects. It is thought that the present study may contribute to the development and design of new anticancer and antimicrobial drugs, especially in the field of cancer research and pharmacology. In addition, it was concluded that the studies on the medical potential of E. italicum should be expanded and more comprehensive studies should be conducted.